2017
DOI: 10.17770/etr2017vol1.2635
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Biological Properties of the Lake Blue Clay

Abstract: In this paper the chemical and biological properties of the lake blue clay are explored. A blue clay bed layer was found under the sapropel layer in the lake Plusons (area 4.8 km2, Ludza countries, Latvia). It has been determined that the lake Plusons blue clay has a colloid composition, which contains Na, Mg, K, Ca, Fe, Cr, Mn, Co, Ni, Cu, Zn, Cd, Pb, Al, Ag, Ba. In samples Candida albicans, Pseudomona aeruginosa, Staphylococcus aureus and a total number of aerobic mezofile bacterium have been defined. In mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The previously implemented research of the lake Plusons identified clay sediments [5], clay locations were found in lake Zeiļi as well. There are 2256 lakes in Latvia with the total area equal to 1001 km 2 , which stands for 1.5% of the territory of Latvia, that provides great scientific interest in terms of resource application in industry.…”
Section: Introductionmentioning
confidence: 88%
“…The previously implemented research of the lake Plusons identified clay sediments [5], clay locations were found in lake Zeiļi as well. There are 2256 lakes in Latvia with the total area equal to 1001 km 2 , which stands for 1.5% of the territory of Latvia, that provides great scientific interest in terms of resource application in industry.…”
Section: Introductionmentioning
confidence: 88%
“…Lake clay effect can be different from lithospheric clay considering that lake clay has formed in different environment and is covered by sapropel layer which medical effectivity has been proven. Considering lake clay chemical parameters, granulometric content, specific surface area and adsorption capacity, lake clay is suitable for cosmetic and dermatological application [12], [13]. However, the presence of some microorganisms in the clay presents the risk of infection, spoilage of the product during storage.…”
Section: Introductionmentioning
confidence: 99%
“…Lake Plusons research [2] identified clay sediments, clay was located in lake Zeiļu as well. Lake sediment survey is a complicated process that consumes both time and money.…”
mentioning
confidence: 99%